2020
DOI: 10.1080/23802359.2019.1660252
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Magnolia delavayi, a threatened species endemic to Southwest China

Abstract: Magnolia delavayi, a threatened plant endemic to Southwest China, is of great importance for landscaping because of its lotus-like creamy flowers. In this study, the complete chloroplast (cp) genome of M. delavayi was assembled based on the Illumina sequences. The cp genome of M. delavayi was 159,470 bp in length and contained a pair of inverted regions (IR, 26,409 bp) which were separated by the small single copy (SSC, 18,760 bp) and the large single copy (LSC, 87,892 bp) regions. It encoded 132 genes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…The newly assembled plastomes had lengths of about 160 kb ( Table 1 ), which is consistent with the lengths observed in previously assembled Magnolia plastomes [ 40 , 41 , 42 , 43 , 44 , 45 ]; partition lengths (LSC, IR, and SSC regions) were also consistent and similar to those observed in previous studies. For the GC content, other studies have found similar values [ 40 ], while for gene content, the previously annotated Magnoliaceae plastomes presented between 113 and 131 genes [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The newly assembled plastomes had lengths of about 160 kb ( Table 1 ), which is consistent with the lengths observed in previously assembled Magnolia plastomes [ 40 , 41 , 42 , 43 , 44 , 45 ]; partition lengths (LSC, IR, and SSC regions) were also consistent and similar to those observed in previous studies. For the GC content, other studies have found similar values [ 40 ], while for gene content, the previously annotated Magnoliaceae plastomes presented between 113 and 131 genes [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…WGS, followed by the use of assembly tools, has resulted in an effective manner to obtain chloroplast genomes for different families of angiosperms [ 13 , 31 , 32 , 33 ], as well as of different Magnoliaceae species [ 40 , 41 , 42 , 44 ]. In this study, the plastomes of 15 Neotropical Magnolia species were assembled through the use of short Illumina reads and the GetOrganelle assembler.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Identical findings have been reported in other species, such as Magnolia polytepala [ 39 ], Magnolia delavayi [ 40 ] and Datura stramonium [ 41 ].…”
Section: Discussionsupporting
confidence: 84%